Nonequilibrium phase transitions in stochastic systems with coloured fluctuations - Kharchenko, D.O.; Olemskoi, A.I.; Knyaz, I.A. (Condensed Matter Physics, 2006)
We study the behaviour of a class of stochastic spatially extended systems exhibiting transition to absorbing configurations, reentrant noise induced phase transitions and phase transitions induced by noise crosscorrelations. We discuss the behaviour of the system in the presence of multiplicative fluctuations: a possibility of escaping from the absorbing state and the nature of disordered phase appearing beyond the second critical point of the reentrant phase transition. Making use of the mean field approach we have shown that noise cross-correlations lead to continuous, discontinuous and reentrant phase transitions.